(untitled) (Swiss Medical Weekly, 2019)
BACKGROUND Choice of antibiotics for complicated appendicitis should address local antibiotic resistance patterns. As our local data showed a less than 15% resistance of Escherichia coli to co-amoxicillin (amoxicillin + clavulanic acid), we opted for this antibiotic in 2013. Subsequently, the increasing prevalence of Pseudomonas aeruginosa challenged this choice. AIM OF THE STUDY The aim of this study was to describe the bacteriology of peritoneal swabs from cases of complicated appendicitis in our paediatric patients, and to determine the risk of infectious complications (wound and/or intra-abdominal abscesses). METHODS We designed a retrospective cohort study including all children (<18 years old) who had surgery for complicated appendicitis between 1 January 2010 and 31 December 2016 and had a peritoneal swab culture. Microbiological results are presented descriptively. Univariate analyses were performed for potential determinants of infectious complications. All variables with a p-value <0.05 were then included in a multivariable logistic regression model, for which adjusted odds ratios (OR) and 95% confidence intervals (CI) were calculated. RESULTS One hundred and thirty-three patients were treated for complicated appendicitis and had cultures of peritoneal fluid. Median age was 9.5 years old (IQR 5.7–12.4), and there were 53 girls (40%). E. coli was isolated in 94 patients (71%) and was resistant to co-amoxicillin in 14% of cases. P. aeruginosa was isolated in 31 patients (23%). The rate of infectious complications was 38% (8/21 patients) when the empiric antibiotic did not cover P. aeruginosa and 0% (0/10 patients) when P. aeruginosa was covered adequately (p = 0.03). In a multivariable analysis, only co-amoxicillin-resistant E. coli significantly predicted infectious complications (OR 4.7; 95% CI 1.4–16.6; p = 0.015). CONCLUSION Results of the multivariable analysis of this small, retrospective study revealed a statistically significant increase in the risk of postoperative complications in the presence of co-amoxicillin-resistant E. coli. The choice of antibiotic should be adapted accordingly. More data are needed to justify the systematic coverage of P. aeruginosa in children with complicated appendicitis.